THE ULTIMATE SACRIFICE. LITERARY REFLECTIONS OF ASSASSINATION AND MURDER AS A SOCIAL GESTURE - Janoušek, Pavel (Bohemica Olomucensia, 2022)
The study is devoted to the topic of the assassination of the prominent politician and the Minister of Finance of the newly established Czechoslovak Republic, Alois Rašín (1867-1923). The author traces the reflection of this event in contemporary journalism, literary works and drama, describes the way in which authors portrayed it depending on their political orientation and their relationship to the ideas of the First Republic. In addition to the depiction of the assassination itself, the authors discussed the question of whether a violent solution is a justifiable method of political struggle.
Keywords: Political assassinations; Alois Rašín; politicisation of literature; Viktor Dyk; Stanislav Lom; Jiří Wolker; Jaroslav Hilbert; Ivan Olbracht; Vítězslav Nezval; Vladislav Vančura